2014
DOI: 10.1111/exd.12337
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induced by resveratrol suppresses αMSH‐induced melanogenesis

Abstract: Autophagy degrades cellular components and organelles through a cooperative process involving autophagosomes and lysosomes. Although autophagy is known to mainly regulate the turnover of cellular components, the role of autophagy in melanogenesis has not been well addressed. Here, we show that inhibition of autophagy suppresses the antimelanogenesis activity of resveratrol (RSV), a well‐known antimelanogenic agent. RSV strongly increased autophagy in melanocytes. However, the depletion of ATG5 significantly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 16 publications
(1 reference statement)
0
31
0
Order By: Relevance
“…Therefore, reduced melanosome degradation could be expected as a mechanism of ARG2 responsible for increased pigmentation. Melanosomes are degraded by autophagy through delivering targeted materials to lysosomes (Kim, Chang, et al., ). Considering that conjugation of Atg12 to Atg5 and conjugation of phosphatidylethanolamine to LC3‐I to create LC3‐II are the main systems contributing to the expansion of phagophore (Weidberg, Shvets, & Elazar, ; Wu et al., ), decreased protein levels of Atg12‐5 to an extent such that they were not less than those of Atg12 or Atg5 and protein levels of LC3‐II to an extent such that they were more than those of LC3‐I caused by ARG2 overexpression regardless of starvation (Figure a,c), with opposite results caused by ARG2 knock‐down (Figure a) suggested that ARG2 could reduce autophagy through inhibiting autophagosome elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reduced melanosome degradation could be expected as a mechanism of ARG2 responsible for increased pigmentation. Melanosomes are degraded by autophagy through delivering targeted materials to lysosomes (Kim, Chang, et al., ). Considering that conjugation of Atg12 to Atg5 and conjugation of phosphatidylethanolamine to LC3‐I to create LC3‐II are the main systems contributing to the expansion of phagophore (Weidberg, Shvets, & Elazar, ; Wu et al., ), decreased protein levels of Atg12‐5 to an extent such that they were not less than those of Atg12 or Atg5 and protein levels of LC3‐II to an extent such that they were more than those of LC3‐I caused by ARG2 overexpression regardless of starvation (Figure a,c), with opposite results caused by ARG2 knock‐down (Figure a) suggested that ARG2 could reduce autophagy through inhibiting autophagosome elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol inhibits melanogenesis by at least four different mechanisms: (1) in human melanocyte cultures, resveratrol inhibited tyrosinase synthesis and activity along with accelerated transport of newly synthesized tyrosinase to proteasomal complex, without dramatic alterations in mRNA levels of either melanocytic microphthalmia-associated transcription factor (MIFT) or tyrosinase [205]; (2) in melan-A cells, inhibition of melanogenesis by resveratrol is via induction of autophagy, leading to reduction in α melanocyte-stimulating hormone levels [206]. e latter stimulates melanin production and release via activation of melanocortin-1 receptor.…”
Section: Othersmentioning
confidence: 99%
“…In addition to its well-established primary function, autophagy is recently reported to have conserved roles in the differentiation and development processes because it can drive the rapid cellular changes necessary for proper differentiation and/or development 7 . In mammals, autophagy is essential to many physiological and pathological processes, such as preimplantation development, 8 exocytosis of the granules from the Paneth cells, 9 polarized secretion of the lysosomal content in osteoclasts, 10 biogenesis of melanosomes, 11 cell differentiation during erythropoiesis, 12 lymphopoeisis, 13 and adipogenesis. 14 Accordingly, it is believed that autophagy could ""kill 2 birds with one stone"" during cellular differentiation because, in addition to eliminating the pre-existing materials, it provides support for the subsequent creation of new components.…”
Section: Introductionmentioning
confidence: 99%